2022
DOI: 10.3390/foods11152269
|View full text |Cite
|
Sign up to set email alerts
|

Brucella spp. Contamination in Artisanal Unpasteurized Dairy Products: An Emerging Foodborne Threat in Tunisia

Abstract: Brucellosis is a worldwide zoonotic disease transmitted to humans, predominantly by the consumption of contaminated raw milk and dairy products. This study aimed to investigate the occurrence of Brucella spp. in 200 raw milk, ricotta, and artisan fresh cheese samples, collected from individual marketing points in four districts in Tunisia. Samples were analyzed for the presence of Brucella spp. by IS711-based real-time PCR assay. Positive samples were further analyzed by qPCR for B. melitensis and B. abortus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These tests are considered more sensitive but less specific than MRT (Aggad & Boukraa, 2006 ), also these tests are less sensitive than the ELISA test, as the sensitivity of direct milk-ELISA is 95% - 96.5% and specificity of 99% - 100% according to (Jalali et al , 2003 ; Kerby et al , 1997 ; Nielsen et al , 1996; Kerkhofs et al , 1990 ; Sutherhand et al , 1986). In contrast, our results lower than that mentioned by (Kang’ethe et al ., 2000 ) in raw milk which ranged from 3.4% to 3.9% with MRT, and 2.4-4.9% with a milk-ELISA test in Kenya, and also lower than that recorded cow’s milk with MRT test (4.0%) by in Azerbaijan (Aliyev et al ., 2022 ), Tunisia (Béjaoui et al ., 2022 ), Egypt (Nofal et al ., 2017 ), and in Algeria (Aggad & Boukraa, 2006 ). No significant difference was observed in the prevalence rate of brucella among the animal by using the Milk-Ring test or by using the Milk-ELISA test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests are considered more sensitive but less specific than MRT (Aggad & Boukraa, 2006 ), also these tests are less sensitive than the ELISA test, as the sensitivity of direct milk-ELISA is 95% - 96.5% and specificity of 99% - 100% according to (Jalali et al , 2003 ; Kerby et al , 1997 ; Nielsen et al , 1996; Kerkhofs et al , 1990 ; Sutherhand et al , 1986). In contrast, our results lower than that mentioned by (Kang’ethe et al ., 2000 ) in raw milk which ranged from 3.4% to 3.9% with MRT, and 2.4-4.9% with a milk-ELISA test in Kenya, and also lower than that recorded cow’s milk with MRT test (4.0%) by in Azerbaijan (Aliyev et al ., 2022 ), Tunisia (Béjaoui et al ., 2022 ), Egypt (Nofal et al ., 2017 ), and in Algeria (Aggad & Boukraa, 2006 ). No significant difference was observed in the prevalence rate of brucella among the animal by using the Milk-Ring test or by using the Milk-ELISA test.…”
Section: Discussionmentioning
confidence: 99%
“…Investagating the Brucella spp. in 200 raw milk, ricotta, and artisan fresh cheese samples, collected from individual marketing points in four districts in Tunisia was done by (Béjaoui et al, 2022) who found 31.3%, and B. melitensis was detected in 5.3% of positive samples. A percentage of 49.3% of samples co-harbored both species, while 14% of the Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Raw or poorly processed foods, such as milk and dairy products, meat, and poultry, can be contaminated with different bacteria, such as Bacillus cereus [ 11 ], Brucella spp. [ 12 ], Campylobacter spp. [ 13 ], Clostridium difficile ( C. difficile ) [ 14 ], Escherichia coli ( E. coli ) [ 15 ], Staphylococcus aureus ( S. aureus ) [ 16 ], or Yersinia spp.…”
Section: The Impact Of Bacterial Activitymentioning
confidence: 99%
“…Gram-negative, non-spore-forming and nonencapsulated cocco bacilli; can infect animals and humans, causing wide clinical manifestations: intermittent fever, headache, nausea, vomiting, night sweats, progressive deterioration in visual function, periorbital pain, and other impacts in hepatobiliary, genitourinary, musculoskeletal, cardiovascular, and integumentary systems; transmitted to humans mainly through contaminated raw milk and dairy products [12,32,33] Campylobacter spp.…”
Section: Bacillus Cereusmentioning
confidence: 99%
“…Brucella can also be transmitted through direct contact with aborted materials, venereal contact (though rare), blood transfusions, and tissue transplantation. Finally, in areas where Brucella is common, individuals may be exposed to the bacteria through direct or indirect contact with their mouth, eyes, or respiratory system [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%